Cellular mechanisms underlying Pax3-related neural tube defects and their prevention by folic acid - Sonia Sudiwala; Alexandra Palmer; Valentina Massa; Alan J. Burns; Louisa P. E. Dunlevy; Sandra C. P. de Castro; Dawn Savery; Kit-Yi Leung; Andrew J. Copp; Nicholas D. E. Greene (The Company of Biologists, 2019)
Neural tube defects (NTDs), including spina bifida and anencephaly, are among the most common birth defects worldwide, but their underlying genetic and cellular causes are not well understood. Some NTDs are preventable by supplemental folic acid. However, despite widespread use of folic acid supplements and implementation of food fortification in many countries, the protective mechanism is unclear. Pax3 mutant (splotch; Sp2H) mice provide a model in which NTDs are preventable by folic acid and exacerbated by maternal folate deficiency. Here, we found that cell proliferation was diminished in the dorsal neuroepithelium of mutant embryos, corresponding to the region of abolished Pax3 function. This was accompanied by premature neuronal differentiation in the prospective midbrain. Contrary to previous reports, we did not find evidence that increased apoptosis could underlie failed neural tube closure in Pax3 mutant embryos, nor that inhibition of apoptosis could prevent NTDs. These findings suggest that Pax3 functions to maintain the neuroepithelium in a proliferative, undifferentiated state, allowing neurulation to proceed. NTDs in Pax3 mutants were not associated with abnormal abundance of specific folates and were not prevented by formate, a one-carbon donor to folate metabolism. Supplemental folic acid restored proliferation in the cranial neuroepithelium. This effect was mediated by enhanced progression of the cell cycle from S to G2 phase, specifically in the Pax3 mutant dorsal neuroepithelium. We propose that the cell-cycle-promoting effect of folic acid compensates for the loss of Pax3 and thereby prevents cranial NTDs.